The Challenge of Islamic Economics - Muhammad Anwar (International Institute of Islamic Thought, 1986)
Muhammad Akram Khan, the well-known Islamic economist, is presently Director-General in the Audit and Accounts Services of the government of Pakistan. He is a prolific writer and scholar with Islamic inspiration and a strong grip on the subject. He has written dozens of articles and books on Islamic economics since 1965 in English and Urdu. His works have been published by organizations and journals of national and international repute. Two of his very important works are “Economic Teachings of Prophet Muhammad (PBUH)” and “Islamic Economics: Annotated Sources in English and Urdu.” The first book is a classified compilation of ahadith relating to Islamic economics and is being published by the Islamic Research Academy, Lahore. It is a monumental work that may turn out to be an indispensable reference on Islamic economics. The second book contains 1,300 abstracts classified into approximately forty headings. It is the first annotated bibliography on Islamic economics. “The Challenge of Islamic Economics,” the book under review, is made up of three papers written, respectively, for the “Journal of Research in Islamic Economics” in 1983, “the Third International Seminar on Islamic Thought,” held under the auspices of the International Institute of Islamic Thought in Kuala Lumpur in July 1984, and the “International Seminar on Islamic Economics” held at Sokoto in February 1985. They make up chapters one, two, and three respectively. The book is addressed to the teachers and researchers in Islamic economics. It informs its readers of the nature, scope, and methodology of this discipline. It points out some of the strengths and weaknesses in the literatme dealing with this subject and advances an approach for teaching Islamic economics. This book, like most of the author‘s writings, is logical, consistent, and thought--provoking ...